On Lithuanian-Latvian Theatrical Relations - Stasys Skrodenis (Literatūra (Vilnius))
There are published letters and memoirs of the Latvian cultural worker and writer Karlis Freinbergs (1884-1967). In his letters to Lithuanian writer Liudas Gira written in 1922-24 one can find the material of great interest on the beginning of collaboration of Lithuanian and Latvian theatres, on Latvian National Theatre's preparation for the first tour in Lithuania. The tour took place in 1924 and was a great success. K. Freinbergs and Janis Rainis, the Director of Latvian National Theatre, had done great services to it.